BIOCHEMICAL ESTIMATION OF GLYCOGEN LEVELS IN THE HAEMOCYTES OF FRESHWATER CRAB BARYTELPHUSA CUNICULARIS - NAYAB ANSARI (International Journal of Pharma and Bio Sciences, 2016)
The haemocytes found in the blood of crustaceans are the main mediators of host defence against infections in crustaceans . Glucose is the principal monosaccharides present in the hemolymph of crustaceans .Glucose is stored in the form of glycogen .The stored glycogen is utilized in moulting ,adaptation to hypoxia and /or anoxia, osmoregulation and during fasting periods .The variation in glucose in the haemolympatic glucose seem to be related to the reproductive period of the species ,food availability and degree of environmental exploration .these factors led to different metabolic adjustment in distinct species of crustaceans. In this study the biochemical glycogen analysis was estimated in the haemocytes of both male and female freshwater crabs Barytelphusa cunicularis. The results showed that the average carbohydrate per cells in females is significantly more than that of males.